Large-scale asset purchases by the Federal Reserve: Did they work? - Joseph Gagnon; Matthew Raskin; Julie Remache; Brian Sack (Federal Reserve Bank of New York, 2010)
Since December 2008, the Federal Reserve's traditional policy instrument, the target federal funds rate, has been effectively at its lower bound of zero. In order to further ease the stance of monetary policy as the economic outlook deteriorated, the Federal Reserve purchased substantial quantities of assets with medium and long maturities. In this paper, we explain how these purchases were implemented and discuss the mechanisms through which they can affect the economy. We present evidence that the purchases led to economically meaningful and long-lasting reductions in longer-term interest rates on a range of securities, including securities that were not included in the purchase programs. These reductions in interest rates primarily reflect lower risk premiums, including term premiums, rather than lower expectations of future short-term interest rates.
Keywords: E43; E44; E52; E58; G12; 330; Term premium; portfolio balance; zero bound; monetary policy; duration; bond yield; Finanzmarktkrise; Offenmarktpolitik; Asset-backed security; Hypothek; Schatzpapier; Wirkungsanalyse; USA